Application of Mycoremediation in Spent Engine Oil - Ho, Cheng Cheng (2017)
Improper disposal and spillage of spent engine oil into the environment will lead to water and soil pollution. Environmental pollution is becoming a major worldwide problem as it will lead to adverse health effects in humans through the food chain. In order to overcome this problem, mycoremediation as an effective and inexpensive alternative is employed in cleaning up engine oil pollution. The first objective of this study was to screen for potential fungi in tolerating spent engine oil by using BHB as selective media. Fungi that were able to grow in BHB supplied with spent engine oil were identified as potential fungi in utilizing spent engine oil as carbon source. The second objective of this study was focused on determination of effectiveness of potential fungi in degrading spent engine oil via confirmatory test by calculating the percentage of degradation of spent engine oil. Six species of fungi namely Mucor sp., Aspergillus flavus, Candida sp., Aspergillus niger, Aspergillus nidulans and Trichoderma sp. Were tested in this study. The result showed that Mucor sp. and Trichoderma sp. demonstrated high tolerance towards spent engine oil as indicated by its heavy growth rate, Aspergillus nidulans, Aspergillus niger and Candida sp. showed moderate tolerance ability towards spent engine oil as denoted by its moderate growth rate whereas Aspergillus flavus was intolerant to spent engine oil as indicated by its absence growth. In the confirmatory test Mucor sp. (42.68%) was indentified as the most effective fungi in degrading spent engine oil, followed by Aspergillus nidulans (39.32%), Aspergillus niger (37.42%), Trichoderma sp. (36.69%), Candida sp. (36.59%) while Aspergillus flavus (33.37%) was identified as the least effective fungi in degrading spent engine oil. Therefore, it was concluded that Mucor sp. was identified as the fungi with the most potential for application in mycoremediation of spent engine oil due to its high growth rate and highst percentage of degradation of spent engine oil as compared to other fungi species in this study.